Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 6 - Section 6.5 - A General Factoring Strategy - Exercise Set - Page 463: 97


$ 2xy(x-y)(5x-2y)$

Work Step by Step

$ 10x^{3}y-14x^{2}y^{2}+4xy^{3}\qquad$... factor out the common term, $2xy$ $=2xy(5x^{2}-7xy+2y^{2})$ ... Searching for two factors of $ac=10$ whose sum is $b=-7,$ we find$\qquad-5$ and $-2.$ Rewrite the middle term and factor in pairs: $=2xy(5x^{2}-5xy-2xy+2y^{2})=$ $=2xy[5x(x-y)-2y(x-y)]$ =$ 2xy(x-y)(5x-2y)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.